HUBUNGAN ANTARA FEAR OF MISSING OUT (FoMO) DENGAN IMPULSIVE BUYING PADA SISWI PENGGUNA TIKTOK DI SMA DON BOSCO PADANG - Anggun Mehenry Florencia; Mita Fani Tri Mutya; Frihapma Semita Ade (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of social media, particularly TikTok, has transformed patterns of social interaction and adolescent consumer behavior. Exposure to viral content, brief promotional messages, and live shopping features encourages the emergence of impulsive buying behavior, especially among female adolescents. One psychological factor believed to contribute to this phenomenon is Fear of Missing Out (FoMO), defined as feelings of anxiety and fear of being left behind current trends or popular social experiences. This study aims to examine the relationship between Fear of Missing Out (FoMO) and impulsive buying among female TikTok users at SMA Don Bosco Padang. The study employed a quantitative approach with a correlational research design. The participants consisted of 143 female students of SMA Don Bosco Padang who actively use TikTok, selected through purposive sampling. Data were collected using a FoMO scale adapted from Daravit (2021) based on the aspects proposed by Przybylski et al. (2013), and an Impulsive Buying scale adapted from Elnina (2022) based on the aspects proposed by Verplanken and Herabadi (2001). Data analysis was conducted using Pearson Product Moment correlation. The results indicated a positive and significant relationship between FoMO and impulsive buying, meaning that higher levels of FoMO among students are associated with a greater tendency toward impulsive buying. These findings suggest that social anxiety and emotional impulses driven by FoMO play an important role in adolescent consumption behavior. This study provides practical implications for schools and students in enhancing digital literacy and self-control in social media use and shopping behavior.